Analysis of the Effect of Currency Exchange Rate, Broad Money (M3) and Oil Prices on Inflation in India - Sharma, Shikha; Dahiya, Manju (International Journal of Economics and Financial Issues, 2023)
The main goal of any government is to keep the inflation rate low and generally constant. However, the economy is threatened by unbridled inflation. Therefore, it is important to understand the factors that affect inflation rates. Information on consumer price index, inflation rate, exchange rate and money supply has been collected from secondary data sources for India. Vector autocorrelation model (VECM) is used for data analysis. In addition, Lagrange multiplier test and Jarque-Bera test were used to determine whether the relationships of the variables are normal. The results showed a short run relationship between inflation and exchange rates. In the long run, there is a poor relationship between the two. Due to the absence of one of the criteria, the VECM cannot demonstrate long-run causality between the two circumstances. The results show that none of the lagged values of broad money are interesting.